Facile Solid‐State Growth of 3D Well‐Interconnected Nitrogen‐Rich Carbon Nanotube–Graphene Hybrid Architectures for Lithium–Sulfur Batteries. (9th December 2015) - Ding, Yuan‐Li; Kopold, Peter; Hahn, Kersten; van Aken, Peter A.; Maier, Joachim; Yu, Yan
Abstract : Constructing 3D carbon structures built from carbon nanotubes (CNTs) and graphene has been considered as an effective approach to achieve superior properties in energy conversion and storage because of the synergistic combination of the advantages of each building block. Herein, a facile solid‐state growth strategy is reported for the first time to fabricate highly nitrogen doped CNT–graphene 3D nanostructures without the necessity to use chemical vapor deposition. As cathode hosts for lithium–sulfur batteries, the hybrid architectures exhibit reversible capacities of 1314 and 922 mAh g −1 at 0.2 and 1 C, respectively, and a capacity retention of 97% after 200 cycles at a high rate of 2 C, revealing their great potential for energy storage application. Abstract : Using a facile and green solid‐state growth strategy, 3D, well‐interconnected, highly nitrogen‐doped carbon nanotube–graphene hybrid structures are designed and fabricated by using Ni foam as growth substrate and catalyst, glucose as carbon sources, and dicyandiamide as nitrogen sources. When used as cathode hosts for Li–S batteries, the obtained product shows superior lithium‐storage capability.